(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2026)
Paronychia is a common tropical infection affecting the periungual skin, often involving bacterial and fungal pathogens, such as Staphylococcus aureus, Pseudomonas spp., and Candida albicans. This study evaluated in vitro antimicrobial efficacy of kenicide, a herbal formulation of Glycyrrhiza glabra, as a potential topical alternative to conventional antibiotics. Among various extraction methods, the glacial acetic acid extract exhibited superior antimicrobial activity against reference and clinical isolates. All extracts demonstrated hemolytic activity, with the ethanol extract showing the highest toxicity. Cytotoxicity assays in Artemia cysts revealed an LD50 of 4.88% (w/v), indicating notable toxicity. Given these cytotoxic and hemolytic effects, Kenicide appears suitable only for topical use. Further in vivo safety evaluations in animal models are warranted before clinical application. Dhaka Univ. J. Pharm. Sci. 25(1): 29-37, 2026 (June)